Classification of radiological objects at the exit of accelerators with a dose-rate constraint. (November 2020) - Frosio, Thomas; Dumont, Gerald; Froeschl, Robert; Iliopoulou, Elpida; Magistris, Matteo; Menaa, Nabil; Roesler, Stefan; Theis, Chris; Vincke, Heinz; Vincke, Helmut
Abstract: Maintenance activities and operations of high-energy particle accelerators can lead to the collection of radioactive equipment as well as waste materials. In order to ensure their proper classification as radioactive or non-radioactive, one has to quantify the activities of radionuclides produced. According to the regulatory requirements in Switzerland, these activities need to be compared with nuclide-specific clearance limits. In particular, a new set of clearance limits was introduced by the Swiss authorities in January 2018, leading to more conservative values for a number of relevant radionuclides. We describe in this paper a new methodology based on dose-rate measurements to classify potentially radioactive objects at the exit of the CERN accelerator complex. This methodology concerns the specific material compositions typically found at CERN and takes into account the latest clearance limits introduced by the Swiss authorities. Highlights: Classification of radiological objects with dose-rate measurement . New methodology for clearance of radiological objects . Classification of radiological objects at the exit of accelerators using calculation codes.